Strategi Pengembangan Dan Peningkatan Literasi Numerasi Dari Sudut Negeri Di SD Negeri 016406 - Guntur Maha Putra; Melni Kurnia; Nur Rizky Ardianty Harahap; Devi Novianti; Agustina Sitorus (STMIK Royal, 2023)
Abstract: Campus teaching activities are motivated by various sectors, one of which is to prepare Indonesian student competencies to face social, cultural, work and technological advances / rapid times, as well as to improve the quality of education for the better. The problems found with partners are focused on the lack of adaptation of technology in management and the learning process in the classroom. The stages/methods of carrying out activities include starting with pre-assignment, assignment to post-assignment. Based on the results of the implementation of activities aimed at increasing students' literacy and numeracy that have been carried out for approximately 5 months, this third campus teaching program received a positive response from the principal, school committee, teacher council, students and guardians of SD Negeri 016406 Gonting Malaha. This is evidenced from the initial acceptance of the campus teaching team which was greeted with pleasure by school stakeholders and the enthusiasm of students in participating in each lesson. Class teachers are also greatly helped by having campus students teach in managing classes and assisting in the use of learning technology. Not only in the learning sector, schools are also greatly helped by the existence of campus students teaching in organizing and managing school administration in the form of reactivating previously abandoned school libraries, compiling correspondence archives and implementing routine gymnastics programs every morning which has not been done before. The results obtained in the technology adaptation of the students also introduced teachers and students directly to the use of information technology and learning resources that are useful in the development and improvement of student literacy and numeracy, for example the use of YouTube and other learning resources.Keywords: campus teaching; administration; technology; literacy; numeration Abstrak: Kegiatan kampus mengajar salah satunya adalah untuk menyiapkan kompetensi mahasiswa indonesia menghadapi perubahan sosial, budaya, dunia kerja dan kemajuan teknologi / zaman yang pesat, serta guna untuk meningkatkan mutu pendidikan menjadi lebih baik (Khotimah et al., 2021). Permasalahan yang ditemukan pada mitra dititikberatkan pada kurangnya adaptasi teknologi dalam manajemen maupun proses pembelajaran di kelas. Berdasarkan hasil pelaksanaan kegiatan yang bertujuan untuk meningkatkan literasi dan numerasi siswa yang telah dilakukan selama kurang lebih 5 bulan, program kampus mengajar angkatan 3 ini mendapatkan respon positif baik dari kepala sekolah, komite sekolah, dewan guru, siswa serta wali murid SD Negeri 016406 Gonting Malaha. Hal ini dibuktikan dari awal penerimaan tim kampus mengajar yang disambut dengan rasa senang oleh stakeholder sekolah dan antusiasme siswa dalam mengikuti setiap pembelajaran. Tahapan/metode pelaksanaan kegiatan diantaranya diawali dengan pra-penugasan, penugasan sampai dengan pasca penugasan. Guru kelas juga sangat terbantu dengan adanya mahasiswa kampus mengajar dalam mengelola kelas dan membantu pendampingan dalam penggunaan teknologi pembelajaran. Tidak hanya pada sektor pembelajaran, sekolah juga sangat terbantu dengan adanya mahasiswa kampus mengajar dalam menata dan mengelola administrasi sekolah berupa pengaktifan kembali perpustakaan sekolah yang terbengkalai sebelumnya, penyusunan arsip surat menyurat dan program pelaksanaan senam rutin setiap pagi yang belum ada dilakukan sebelumnya. Hasil yang diperoleh dalam adaptasi teknologi para mahasiswa juga memperkenalkan kepada guru maupun siswa secara langsung mengenai pemanfaatan teknologi informasi maupun sumber-sumber pembelajaran yang berguna dalam pengembangan dan peningkatan literasi serta numerasi siswa misalnya penggunaan youtube maupun sumber belajar lainnya.Kata kunci: kampus mengajar; administrasi; teknologi; literasi; numerasi